The Viscosity Splitting Solutions of the Navier-Stokes Equations (Journal of Partial Differential Equations, 2020)
The solutions of the initial boundary value problems or the Navier-Stokes equations are constructed by means of a viscosity splitting scheme. Convergence results are proved.
Keywords: Navier-Stokes equations; Euler equations; viscosity; split; convergence